Attributing discrimination to weight: Associations with well-being, self-care, and disease status in patients with type 2 diabetes mellitus - Potter, Lindsey (J Behav Med, 2015)
This study examined the association between attributing self-reported discrimination to weight and diabetes outcomes (glycemic control, diabetes-related distress, and diabetes self-care). A community dwelling sample of 185 adults (mean age = 55.4; 80% White/Caucasian, 65% female) with poorly controlled Type 2 diabetes (HbA1c level ≥7.5%) provided demographic and several self-report measures (including diabetes-related distress, diabetes self-care activities, discrimination, and attributions of discrimination), and had height, weight, and glycated hemoglobin (HbA1c) assessed by trained research staff as part of a larger research study. Individuals who attributed self-reported discrimination to weight had significantly higher HbA1c levels, higher levels of diabetes-related distress, and worse diabetes-related self-care behaviors (general diet, exercise, and glucose testing). These relationships persisted even when controlling for BMI, overall discrimination, depressive symptoms, and demographic characteristics. Results indicate that the perception of weight stigma among individuals with type 2 diabetes is strongly associated with a range of poor diabetes outcomes. Efforts to reduce exposure to and/or teach adaptive coping for weight stigma may benefit patients with type 2 diabetes.